PWE-415 Kappa study to identify inter-observer variability in peri-operative risk assessment. (22nd June 2015) - Mirza, A; Smart, C
Abstract : Introduction: Physiological and Operative Severity Score for the enumeration of Mortality and Morbidity (POSSUM) and subsequently P-POSSUM, has been used routinely in surgery as a tool for auditing peri-operative outcome. Recent reports reviewing provision of unscheduled care, commissioning guidance and the NELA audit put risk assessment as a priority. Accurate quantification of risk in these patients is important as this can affect pre-operative decision making, but 8 of the parameters are subjective in nature. The aim of this study was to identify any variation in reporting peri-operative risk in patients undergoing emergency laparotomy between anaesthetists and surgeons of varying grades. Method: Prospective P-POSSUM data was independently collected for 18 patients undergoing emergency laparotomy by all anaesthetic and surgical team members. Kappa ( k ) score was used to identify inter-observer variability (>80 significant). Results: The median age was 43 (range 24 to 86) years with 8 male and 10 female patients. There was wide variation in reporting of risk especially in objective physiological parameters (cardiac p = 0 .20, respiratory p = 0 .23) and objective operative parameters, operation type (p = 0.16, k =10), peritoneal contamination (p = 0.36, k =43). Overall this lead to poor concordance in operative morbidity ( p = 0 .42, k =56) and mortality ( p = 0 .67, k =49). The anaesthetist predict significantly higher mortality as compared to a general surgeon (p = 0.02). Conclusion: This study has shown wide variation in prediction of peri-operative risk with anaesthetists predicting higher levels. P-POSSUM is a tool designed for surgical audit, not pre-operative risk. Quantative assessment of risk is necessary and anaesthetists and surgeons must both agree before documenting and discussing with patients. Disclosure of interest: None Declared.